Transformation of green fluorescent protein reporter gene into rice Oryza sativa cv. KDML 105 by co-cultivation with agrobacterium - Chanprapa Imjongjirak (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 2000